Preferences of patients with multiple chronic diseases for medication in rural areas of an Eastern Province China: a discrete choice experiment - Li, Xiaona; Ma, Dongping; Feng, Zhiqiang; Gao, Min; Dong, Ping; Shi, Yongli; Li, Ziyuan; Li, Runmin; Yin, Wenqiang; Chen, Zhongming (Frontiers in Medicine, 2024)
Background Multiple Chronic Diseases (MCD) are the co-occurrence of two or more chronic conditions within an individual. Compared to patients with a single chronic disease, those with MCD face challenges related to polypharmacy, which increases the risk of adverse drug events, side effects, and drug–drug interactions. Understanding the specific medication preferences of patients with MCD is crucial to optimize treatment plans and enhance treatment safety. Objective This study aims to evaluate the medication preferences among patients with multiple chronic diseases in rural areas of an eastern province of China. Methods A discrete choice experiment (DCE) was used to measure patients’ medication preferences. According to literature research, expert panel discussions, and in-depth patient interviews, we identified six attributes: monthly out-of-pocket cost, onset speed of action, adverse effects, whether it is covered by health insurance, origin of medications, and types of medications. The conditional logit models (CLM) and mixed logit models (MIXL) were used to evaluate the choice data. Willingness to pay (WTP) was used to reflect the monetary value that patients were willing to pay or receive reimbursement after changes in different attribute levels. Results A total of 956 respondents were included in the analysis. Of which, 68.62% were female, with an average age of 68 years, and 65.89% had a Body Mass Index (BMI) greater than or equal to 24. Statistical significance was observed for all attributes (p < 0.001). The preferred medication for patients encompassed low monthly out-of-pocket costs, rapid onset of action, rare adverse effects, and a preference for Western medicine, health insurance-covered medication and domestic medication. The onset speed of action was a primary consideration for patients, who demonstrated a willingness to pay an additional CNY151.37 per month for a medication with a rapid onset of action. Conclusion Rural patients with multiple chronic diseases preferred medications with rapid onset, rare adverse, Western medications, domestic medication, and health insurance-covered medication. Medical staff can effectively combine the Health Belief Model (HBM) to help patients with multiple chronic diseases improve their confidence and understanding of medication selection, to improve their health management.